When all hell broke loose - Johnstone, William W.; Johnstone, J. A. (Johnstone, William W. Preacher & MacCallister western, 2021)
"It's one of the great mysteries of the Old West. The unexplained disappearance of a hunting party of Prussian nobles who entered the American wilderness--and never returned. Now, years later, the Prussian government demands an explanation. In response, the U.S. Army hires Preacher and Jamie MacCallister to join their search party--along with a band of Prussian soldiers led by the sinister Baron Adalwolf von Kuhner. Some believe it's a hopeless mission, that the original party was slaughtered by the Blackfeet. Others think there may be survivors, most likely women held captive as slaves. But it doesn't take Preacher and MacCallister long to learn the horrible truth... This is no rescue mission. It's a massacre in the making. And when the hunters become the hunted, all hell breaks loose..."--